SPECIFYING THE EFFECTIVE DETERMINANTS OF HOUSE PRICE VOLATILITIES IN IRAN - Murteza Sanjarani Pour; Parviz Nasir Khani; Gholamreza Zamanian; Kamran Barghandan (Economic Review)
The housing sector is one of the key sectors in an economy and its fluctuations could be accompanied with stagnation or expansion in other parts of an economy. Additionally, this sector has an intra-economic role in near to 120 sub-industries which therefore indicates its importance in an economy. Hence, this study examines the effective determinants of house price volatilities using the Engel Granger cointegration technique after modeling the price volatilities under the E-Garch model for the period 1973-2008 in Iran based on Eviews and Mathematica Software. The findings indicate that all variables, including coin price, GDP proxy, volume of money, inflation rate, and house interest rate have a significant impact on the volatilities.